Crystallization and preliminary structure determination of the membrane-bound complex cytochrome c nitrite reductase from Desulfovibrio vulgaris Hildenborough - Rodrigues, M. L. (2019)
The cytochrome c nitrite reductase (cNiR) isolated from Desulfovibrio vulgaris Hildenborough is a membrane-bound complex formed of NrfA and NrfH subunits. The catalytic subunit NrfA is a soluble pentahaem cytochrome c that forms a physiological dimer of about 120 kDa. The electron-donor subunit NrfH is a membrane-anchored tetrahaem cytochrome c of about 18 kDa molecular weight and belongs to the NapC/NirT family of quinol dehydrogenases, for which no structures are known. Crystals of the native cNiR membrane complex, solubilized with dodecylmaltoside detergent (DDM), were obtained using PEG 4K as precipitant. Anomalous diffraction data were measured at the Swiss Light Source to 2.3 Å resolution. Crystals belong to the orthorhombic space group P212121, with unit-cell parameters a = 79.5, b = 256.7, c = 578.2 Å. Molecular-replacement and MAD methods were combined to solve the structure. The data presented reveal that D. vulgaris cNiR contains one NrfH subunit per NrfA dimer.